Effects of Diversification on Profitability and Operating Risk for Brazilian Publicly Traded Companies - Camila Adam; Tatiane Meurer; Moacir Manoel Rodrigues (BBR: Brazilian Business Review)
This study analyzed the effect of industrial and international diversification on the profitability and operational risk of Brazilian companies. The sample comprised 210 publicly traded Brazilian companies, who trade shares on the B3 stock exchange. The results of the study showed that industrially diversified companies both reduce operational risk and increase profitability in terms of return on assets, while companies that are internationally diversified reduce their profitability. As well, the companies that diversify both industrially and internationally, see increasedoperational risk. This study is relevant to the investigation of the relationship of industrial and international diversification in companies' operating results, as it indicates that, in the context of Brazil, industrial diversification tends to improve operating results, with an increase in profitability and a reduction in operating risk.